Comparação das alterações dentoalveolares e tegumentares do tratamento da má oclusão de classe II por meio de elásticos intermaxilares sem e com extração de 2 pré-molares superiores - Marin, Cristina de Almeida Paschotto Pezzo (2015)
Introduction: The objective of this study was to compare, through lateral cephalograms, the dentoalveolar and soft tissue changes produced by the Class II malocclusion treatment protocols through Class II intermaxillary elastics without and with extraction of two maxillary premolars. Material and Methods: A retrospective sample of 44 patients with Class II malocclusion, Division 1, bilateral, at least end to end severity, divided into two groups: group 1: 22 patients (10 males and 12 females) with initial mean age of 18.87 years (min: 9.5 years, max: 47.8 years), initial mean overjet of 7,31mm treated with intermaxillary elastics without tooth extraction; for a mean treatment time of 3.41 years. Group 2: 22 patients (05 males and 17 females), with initial mean age of 18.31 years (min: 11.5 years, max: 48.1 years), initial mean overjet of 6,88mm treated with intermaxillary elastics associated with extraction of two maxillary premolars, for a mean treatment time of 3.02 years. The lateral cephalograms called T1 (before treatment) and T2 (after treatment) was used to compare the cephalometric variables of the initial and final phases of two groups. For intergroup comparison of cephalometric variables, inicial mean age and treatment time, the t test were used; and to compare the sex distribuition and severity of malocclusion the test Qui-quadrado was used. All tests were perfomed using a significant level of 5% (P <0,05). Results: Comparing the changes introduced by the two studied treatment protocols, the significant changes that occurred were the variables 6S.SN (°), 6S-PTV (mm), 1-NB (mm), molar relation and Li- EPlane (mm). During treatment, group 2 had statistically greater mesial movement of the maxillary first molar compared with Group 1. The mandibular incisors showed greater protrusion in Group 1 compared with Group 2. The molar relation showed the maxillary first molar in a most mesial position in Group 2 compared wit Group 1. In the soft-tissue profile a significant alteration was the greater retraction of the lower lip in Group 2 compared with Group 1. In the final (T2) the maxillary molar showed greater mesial movement in Group 2 as compared to Group 1. Conclusion: Both protocols are effective in correcting overjet and canine relationship. The use of intermaxillary elastics without extractions promotes greater protrusion of the lower incisors. The two treatment protocols evaluated, showed similar alterations in maxillary incisors, mandibular first molar, upper lip and nasolabial angle.